Causes and implications of the recent increanse in the reported sex ratio in birth in China - Yi, Zeng; Ping, Tu; Boachang, Gu; Yi, Xu; Bouha, Li; Yongping, Li
tbls.
pp. 283-302
Keywords: Masculinidad; Nacimientos; Declaración de Nacimientos; Aborto; China